Breast cancer targeted/ therapeutic with double and triple fusion Immunotoxins. Issue 200 (June 2020) - Goleij, Zoleikha; Mahmoodzadeh Hosseini, Hamideh; Sedighian, Hamid; Behzadi, Elham; Halabian, Raheleh; Sorouri, Rahim; Imani Fooladi, Abbas Ali
Highlights: The scFv(Herceptin)-PE-STXA and scFv(Herceptin)-PE are a synthetic fusion protein. Immunotoxins incubation dose-dependently reduces the SKBR-3 cells proliferation. The cell ELISA was used to determine the binding ability of immunotoxins to the cell receptor. Imunotoxins can attach to HER2-positive breast cancer cells Abstract: Target-specific transport of therapeutic agents holds promise to increase the efficacy of cancer treatment by decreasing injury to normal tissues and post treatment problems. HER2 is a tumor cell surface marker that is expressed in 25–30 % of breast cancer patients. The significant role of HER2 in cancer development and its biological feature makes it a highly appealing goal for the therapeutic treatment of cancer targeted therapy using HER2 monoclonal antibody. This approach is currently used as a special treatment against breast cancer in some research. In the present study, HER2 monoclonal antibody (mAb), (Herceptin) fused to PE38 by recombinant DNA technology and a new recombinant IT was developed. The scFv(Herceptin)-PE-STXA and scFv(Herceptin)-PE fusions cloned in pET28a and recombinant protein expression was carried out and then the proteins were purified. MCF-7 and SKBR-3 cells were used as HER2-negative and HER2-positive breast cancer cells, respectively. The cytotoxicity of its evaluated using MTT assay. The cell ELISA was used to determine the binding ability of immunotoxins (ITs) to the cell receptor and internalization and apoptosis were also assessed. The results revealed that cell cytotoxicity occurred in SKBR-3 cells in a dose-dependent manner but not in MCF-7 cells. It is possible that this ITs can attach to HER2-positive breast cancer cells and then, internalize and eradicate cancer cells by apoptosis. Here, we concluded that the recombinant ITs have therapeutic potential against HER2-positive breast cancer.